The Bilingual education policy and students' academic achievement - Narvades, Florida Fordeleon 1949- (2004)
An evaluation approach to language program-a combination of a quantitative and a qualitative data analysis within a natural context was used to assess the 1987 Bilingual Education Policy. The study showed that the level of students' academic achievement was, generally, low. It was discovered that while the majority of English and all Science teachers had low levels of English proficiency, some teachers teaching Filipino and Social Studies were Filipino proficient. A great majority of the teacher-respondents were also highly motivated as far as teaching was concerned. A big number of the teachers adhered to both meaning-based and form-based approaches to language teaching.
"December 2004."
Vita.
Thesis (Ph.D. Education : Language Education)--University of the Philippines, Diliman.
Keywords: Education, Bilingual -- Philippines -- Sorsogon; High school seniors -- Philippines -- Sorsogon; Academic achievement -- Philippines -- Sorsogon